Implementation of business process reengineering concept in transforming Nigerian firm: A systematic literature review - Ugwu, Kelechi Enyinna; Njoku, Dr. Charles Odinakachi (Journal of Commerce, Management, and Tourism Studies, 2025)
This study evaluates the implementation of Business Process Reengineering (BPR) in Nigerian firms, with a particular focus on the financial sector and mobile network operators. The primary objective is to examine how BPR contributes to enhancing organizational efficiency, effectiveness, customer satisfaction, service delivery, quality, and continuous improvement. By restructuring business processes through innovative strategies and tools, BPR aims to significantly improve organizational performance. The study adopts a systematic literature review approach, analysing peer-reviewed articles and case studies related to Nigerian financial institutions and mobile service providers. Key sections include an overview of BPR, the tools and techniques employed, the application of Business Action Theory, and the measurable impact of BPR on organizational operations. Through the synthesis of existing literature, the research explores the transformative potential of BPR in terms of operational efficiency, market innovation, and strategic expansion. Findings reveal that BPR has a significant positive impact on Nigerian organizations by fostering better resource utilization, streamlined workflows, and enhanced service delivery. Case studies demonstrate successful implementation in both sectors, where organizations witnessed increased competitiveness and customer satisfaction. The study concludes that BPR holds substantial potential in revolutionizing Nigerian financial and telecommunications sectors by creating pathways for innovation and growth. It recommends that firms adopt strategic planning, ensure optimal resource allocation, and promote change initiatives through sustained leadership and organizational commitment. Additionally, the study provides valuable insights for practitioners and scholars and suggests directions for future research in emerging markets.